Transplant of Induced Pluripotent Stem Cell–Derived Retinal Pigment Epithelium Strips for Macular Degeneration and Retinitis Pigmentosa - Daiki Sakai, MD; Michiko Mandai, MD, PhD; Yasuhiko Hirami, MD, PhD; Midori Yamamoto, BA; Shin-ichiro Ito, MD, PhD; Saori Igarashi, MD; Satoshi Yokota, MD, PhD; Hirofumi Uyama, MD, PhD; Masashi Fujihara, MD, PhD; Akiko Maeda, MD, PhD; Motoki Terada, BS; Mitsuhiro Nishida, MS; et al. (Ophthalmology Science)
Purpose: To explore the safety and efficacy of the allogeneic induced pluripotent stem cell (iPSC)–derived retinal pigment epithelium (RPE) strip transplantation for patients with RPE degeneration. Design: Single-arm, open-label, interventional study. Participants: Three eyes from 3 patients clinically diagnosed with RPE impairment disease; 1 patient had dry age-related macular degeneration (AMD), and remaining 2 patients had MERTK-associated retinitis pigmentosa. Intervention: Allogeneic iPSC-derived RPE strip transplantation was performed by a 25-gauge pars plana vitrectomy. The RPE strips were prepared by incubating iPSC-derived RPE cells in 2-mm-wide grooves in the mold. Artificial retinal detachment was generated using a 38-gauge subretinal cannula, and the RPE strips were injected into the retinal bleb using a 31-gauge cannula with the maximum graft dose limited to 2 strips. Main Outcome Measures: The reduction of RPE abnormal area by the engraftment of transplanted allogeneic iPSC-derived RPE cells, which was measured by analyzing fluorescein angiography with an automated evaluation program at pretransplantation and up to 52 weeks posttransplantation. Results: The primary endpoint of reducing abnormal areas of RPE through the survival of the transplanted graft cells was achieved in all patients at 52 weeks posttransplantation. Visual function assessments confirmed significant vision-related quality of life improvement and potential retinal sensitivity restoration in 1 patient with dry AMD. The successful subretinal delivery of the iPSC-derived RPE strips was confirmed during and immediately after surgery. The engraftment of RPE cells migrated out from the strips was observed using polarization-sensitive OCT specifically and visualized as characteristic hexagonal cells via adaptive optics imaging in all patients. While no serious adverse events occurred, suspected immune reactions to graft cells and epiretinal membrane formation were observed in 1 patient each. Conclusions: A decrease in the RPE abnormal area by reliable delivery of allogeneic iPSC-derived RPE strips was achieved in all 3 cases with no serious adverse events. Further long-term studies and larger cohorts with better preoperative vision are warranted to evaluate the safety and efficacy of RPE strip transplantation. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.